RGO-coated Mn-Ti co-doped sodium ferric fluorophosphate material as well as preparation method and application of rGO-coated Mn-Ti co-doped sodium ferric fluorophosphate material

By using rGO-coated Mn-Ti-coated sodium fluoroferophosphate material in sodium ion battery positive electrode material, the problems of low energy density and poor circulation performance of existing materials are solved, and high energy density and long cycle life are achieved effect.

CN119419245AActive Publication Date: 2025-02-11SHUANGDENG GRP CO LTD

Patent Information

Application Number
CN202411544519.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have low energy density and poor circulation performance, and the structural stability of sodium ferric phosphate fluoride materials have poor electronic conductivity and poor mechanical properties, and process conditions are prone to cracks.

Method used

Using rGO-coated Mn-Ti co-doped sodium fluorogenic ferrophosphate material, the thickness of the coating is coordinated through two ball milling, sintering and hydrothermal reactions, improving electron conductivity and structural stability, and reducing circulation Cracking during the process.

Benefits of technology

The energy density and cyclic stability of the positive electrode material are improved, structural stability and electronic conductivity are enhanced, interface side reactions are reduced, and overall performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419245A_ABST
    Figure CN119419245A_ABST
Patent Text Reader

Abstract

The invention relates to the field of sodium ion battery positive electrode materials, in particular to an rGO-coated Mn-Ti co-doped sodium ferric fluorophosphate material as well as a preparation method and application of the rGO-coated Mn-Ti co-doped sodium ferric fluorophosphate material. The chemical formula of the catalyst is Na2FexMnyTizPO4F (at) rGO, wherein 0.05 < = y < = 0.10, 0.02 < = z < = 0.05, and x + y + z = 1; by optimizing the raw material proportion and sintering conditions and adopting the two-time sintering process of low-temperature pre-sintering-ball milling in the inert atmosphere-secondary sintering, the raw materials are uniformly mixed on the premise that the raw materials are not oxidized and deteriorated by air, the contact area is increased, efficient ion migration and lattice formation among reactants are facilitated, and the purity of the product is improved. The anion F with strong electronegativity is successfully introduced to form a relatively strong binding force with a phosphate group, so that the generation of pyrophosphoric acid is inhibited, and the crystal structure is optimized; through Mn-Ti co-doping, the stability of a voltage platform and a material structure is effectively improved, so that the material has relatively high energy density and relatively long cycle life; meanwhile, a stable interface layer can be formed on the surface of the material through two-dimensional rGO coating, interface side reactions are reduced, and the cycling stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion battery positive electrode materials, and in particular to an rGO-coated Mn-Ti co-doped sodium iron fluoride phosphate material and a preparation method and application thereof. Background Art

[0002] As traditional fossil energy sources are becoming increasingly depleted, various new types of renewable energy have broad application prospects. Among them, sodium-ion batteries, as emerging secondary batteries, have the advantages of abundant resources, low prices, and good safety. Their key technologies are not much different from lithium-ion batteries and have a good technical foundation. In addition, sodium-ion batteries can also achieve wide temperature range discharge and fast charge and discharge. Therefore, sodium-ion batteries are becoming the main choice for large-scale energy storage power stations with relatively low energy density requirements.

[0003] Polyanion cathode materials have become a hot topic in the field of sodium ion battery cathode materials due to their three-dimensional spatial structure, low cost, and high safety. Currently, common sodium ion battery cathode materials still face many challenges such as low energy density and poor cycle performance. For example, Chinese patent document CN116565180A discloses a method for coating the surface of lithium ion battery cathode powder materials, which involves a preparation method for carbon coating the surface of lithium iron phosphate materials. Although compared with lithium iron phosphate materials, sodium fluoride phosphate materials contain Na + and the more electronegative F - However, the fluorinated sodium iron phosphate material has poor structural stability, low intrinsic electronic conductivity, and poor mechanical properties. The process conditions used for lithium iron phosphate materials are directly applied to fluorinated sodium iron phosphate, which can easily lead to cracks and other problems, thereby affecting the material performance. Chinese patent document CN116169264A discloses a carbon-coated sodium-rich pyrophosphate sodium iron phosphate composite positive electrode material and its preparation method and application. Although it is a new material that can be applied to sodium ion batteries, the electronic conductivity of pyrophosphate is low, and it is easy to undergo structural changes during the charge and discharge cycle, resulting in a decrease in the battery voltage platform and a decrease in the overall specific capacity. Summary of the invention

[0004] The purpose of the present invention is to provide a rGO-coated Mn-Ti co-doped sodium fluorophosphate material and a preparation method and application thereof, which can further improve the energy density and cycle performance of the positive electrode material.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] The first aspect of the present invention is to provide a rGO-coated Mn-Ti co-doped sodium fluorophosphate material, the chemical formula of which is Na2Fe x Mn y Ti zPO4F@rGO; wherein, 0.05≤y≤0.10, 0.02≤z≤0.05, x+y+z=1; Fe is +2 valence, Mn is +2 valence, and Ti is +2 valence.

[0007] The second aspect of the present invention is to provide a method for preparing the above-mentioned rGO-coated Mn-Ti co-doped sodium fluoroferric phosphate material, the steps comprising:

[0008] S1, after mixing a sodium source, an iron source, a manganese source, a titanium source, a phosphorus source and a fluorine source in proportion, the mixture is subjected to a first ball milling treatment, a first drying treatment and a pre-sintering treatment in sequence to obtain a primary calcined product;

[0009] S2, subjecting the primary calcined product to a second ball milling treatment, a second drying treatment, and a second sintering treatment in sequence to obtain a Mn-Ti co-doped sodium fluoroferric phosphate material;

[0010] S3, dispersing the Mn-Ti co-doped sodium iron fluoride phosphate material in anhydrous ethanol and performing ultrasonic treatment to obtain a suspension;

[0011] S4. Add the rGO dispersion dropwise into the suspension while continuously stirring, and then sequentially perform hydrothermal treatment, washing treatment and a third drying treatment to obtain the rGO-coated Mn-Ti co-doped sodium iron fluoride phosphate material.

[0012] Preferably, in step S1, the molar ratio of sodium, iron, manganese, titanium, phosphorus and fluorine in the mixture is 2:x:y:z:1:1.

[0013] Preferably, in step S1, the sodium source comprises: at least one of sodium fluoride, sodium acetate, sodium carbonate, sodium citrate, and sodium oxalate;

[0014] The iron source includes: at least one of ferrous oxalate, ferrous sulfate, and ferrous chloride;

[0015] The manganese source includes: at least one of manganese dioxide, manganese trioxide, and manganese oxalate;

[0016] The titanium source includes: at least one of titanium monoxide, titanium dioxide, titanium oxalate, and titanium sulfate;

[0017] The phosphorus source includes: at least one of diammonium phosphate and diammonium hydrogen phosphate;

[0018] The fluorine source includes at least one of sodium fluoride and hydrofluoric acid.

[0019] Preferably, in step S1, the rotation speed of the first ball milling treatment is 300-500 rpm, and the time is 6-8 hours; the mass ratio of the ball milling beads to the mixture is (8-10): 1;

[0020] The temperature of the first drying treatment is 60-100° C. and the time is 8-14 hours.

[0021] Preferably, in step S1, the pre-sintering treatment comprises: pre-passing protective gas at room temperature for 0.5-2h, heating from room temperature to 350-450°C at a rate of 3-5°C / min, and calcining for 2-6h;

[0022] Wherein, the protective gas is at least one of argon, hydrogen argon, nitrogen and helium.

[0023] Preferably, in step S2, the rotation speed of the second ball milling treatment is 400-500 rpm, and the time is 4-6 hours; the mass ratio of the ball milling beads to the first calcined product is (8-10):1;

[0024] The temperature of the second drying treatment is 60-100° C. and the time is 8-14 hours.

[0025] Preferably, in step S2, the secondary sintering treatment comprises: pre-passing protective gas at room temperature for 0.5-2h, heating from room temperature to 550-650°C at a rate of 3-5°C / min, and calcining for 8-12h;

[0026] Wherein, the protective gas is at least one of argon, hydrogen argon, nitrogen and helium.

[0027] Preferably, in step S4, the mass ratio of the Mn-Ti co-doped sodium iron fluoride phosphate material to rGO is 1:(0.005-0.01);

[0028] The temperature of the hydrothermal treatment is 120-140° C. and the reaction time is 6-8 hours.

[0029] The third aspect of the present invention is to provide an application of the above-mentioned rGO-coated Mn-Ti co-doped sodium fluoroferric phosphate material or the rGO-coated Mn-Ti co-doped sodium fluoroferric phosphate material prepared by the above-mentioned preparation method in the positive electrode material of a sodium ion battery.

[0030] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:

[0031] (1) The present invention improves the electronic conductivity of the phosphate material by co-doping Mn-Ti and coating with rGO on the basis of the Na2FePO4F material, while enhancing the structural stability of the material, so that the positive electrode active material has both high energy density and cycle stability; wherein, manganese doping can effectively improve the energy density of the material, and can anchor between the lattices to widen the lattice size and improve the sodium ion transmission rate; low-valent titanium doping can stabilize the lattice structure and improve the cycle stability of the material.

[0032] (2) The present invention can better coordinate the thickness of the coating layer by combining two ball milling and sintering with a hydrothermal reaction to take into account both electronic conductivity and specific capacity, and inhibit the generation of cracks caused by material volume changes during the cycle process, forming a uniform rGO coating layer on the material surface, reducing the interface side reactions between the material and the electrolyte, and improving the problems of low discharge capacity and poor rate performance caused by the low electrical conductivity of the material itself.

[0033] (3) The present invention optimizes the raw material ratio, sintering conditions, and adopts a two-step sintering process of low-temperature pre-sintering-ball milling in an inert atmosphere-secondary sintering, so that the raw materials are uniformly mixed and the contact area is increased without being oxidized and deteriorated by air, which is conducive to efficient ion migration and lattice formation between reactants, and successfully introduces a strong electronegative anion F to form a strong binding force with the phosphate group, inhibiting the formation of pyrophosphate and optimizing the crystal structure. As a polyanionic compound, Na2FePO4F has a narrow and stable charge and discharge curve, and the battery management difficulty is relatively low, which is suitable for large-scale power grid energy storage; through Mn-Ti co-doping, the voltage platform and material structure stability are effectively improved, so that the material has a higher energy density and a longer cycle life; at the same time, the two-dimensional rGO coating, in addition to improving the conductivity, can also form a stable interface layer on the material surface, reduce the occurrence of interface side reactions, and improve the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The rGO-coated Mn-Ti co-doped sodium fluorophosphate material Na2Fe 0.85 Mn 0.1 Ti 0.05 XRD pattern of PO4F@rGO;

[0035] Figure 2 The rGO-coated Mn-Ti co-doped sodium fluorophosphate material Na2Fe 0.85 Mn 0.1 Ti 0.05 SEM image of PO4F@rGO;

[0036] Figure 3 The rGO-coated Mn-Ti co-doped sodium fluorophosphate material Na2Fe 0.85 Mn 0.1 Ti 0.05 Comparison of the charge and discharge curves of PO4F@rGO and undoped Na2FePO4F. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0039] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.

[0040] Example 1

[0041] This embodiment provides a rGO-coated Mn-Ti co-doped sodium fluorophosphate material Na2Fe 0.85 Mn 0.1 Ti 0.05 The preparation method of PO4F@rGO comprises the following steps:

[0042] S1. Sodium acetate, ferrous oxalate, manganese oxalate, titanium oxalate, diammonium hydrogen phosphate and sodium fluoride are mixed in a molar ratio of 1:0.85:0.1:0.05:1:1, and the mixture is subjected to a first ball milling treatment, a first drying treatment and a pre-sintering treatment in sequence to obtain a first calcined product; the molar ratio of sodium, iron, manganese, titanium, phosphorus and fluorine in the mixture is 2:0.85:0.1:0.05:1:1; the rotation speed of the first ball milling treatment is 500 rpm, and the time is 6 hours; the mass ratio of ball milling beads to the mixture is 8:1; the temperature of the first drying treatment is 60°C, and the time is 14 hours; the pre-sintering treatment includes: pre-passing argon gas at room temperature for 1 hour, heating from room temperature to 350°C at a rate of 3°C / min, and calcining for 6 hours;

[0043] S2, the product of the primary calcination is subjected to a second ball milling treatment, a second drying treatment and a second sintering treatment in sequence to obtain a Mn-Ti co-doped sodium fluorophosphate iron material; the rotation speed of the second ball milling treatment is 500 rpm, and the time is 4 hours; the mass ratio of the ball milling beads to the product of the primary calcination is 8:1; the temperature of the second drying treatment is 60°C, and the time is 14 hours; the secondary sintering treatment includes: pre-passing argon gas at room temperature for 1 hour, heating from room temperature to 550°C at a rate of 3°C / min, and calcining for 12 hours;

[0044] S3, dispersing the Mn-Ti co-doped sodium iron fluoride phosphate material in anhydrous ethanol and performing ultrasonic treatment to obtain a suspension;

[0045] S4, adding the rGO dispersion dropwise into the suspension (the mass ratio of Mn-Ti co-doped sodium fluoroferric phosphate material and rGO is 1:0.005), stirring continuously, and then sequentially performing hydrothermal treatment, washing treatment and a third drying treatment to obtain the rGO-coated Mn-Ti co-doped sodium fluoroferric phosphate material Na2Fe 0.85 Mn 0.1 Ti 0.05 PO4F@rGO; the temperature of the hydrothermal treatment is 120°C; and the reaction time is 8h.

[0046] Example 2

[0047] This embodiment provides another rGO-coated Mn-Ti co-doped sodium fluorophosphate material Na2Fe 0.88 Mn 0.08 Ti 0.04 The preparation method of PO4F@rGO comprises the following steps:

[0048] S1. Sodium acetate, ferrous chloride, manganese trioxide, titanium dioxide, diammonium hydrogen phosphate and sodium fluoride are mixed in a molar ratio of 1:0.88:0.04:0.04:1:1, and the mixture is subjected to a first ball milling treatment, a first drying treatment and a pre-sintering treatment in sequence to obtain a first calcined product; the molar ratio of sodium, iron, manganese, titanium, phosphorus and fluorine in the mixture is 2:0.88:0.08:0.04:1:1; the rotation speed of the first ball milling treatment is 300 rpm, and the time is 8 hours; the mass ratio of ball milling beads to the mixture is 9:1; the temperature of the first drying treatment is 80°C, and the time is 12 hours; the pre-sintering treatment includes: pre-passing hydrogen and argon gas at room temperature for 1.5 hours, heating from room temperature to 400°C at a rate of 4°C / min, and calcining for 4 hours;

[0049] S2, the product of the primary calcination is subjected to a second ball milling treatment, a second drying treatment and a second sintering treatment in sequence to obtain a Mn-Ti co-doped sodium fluorophosphate iron material; the rotation speed of the second ball milling treatment is 400 rpm, and the time is 6 hours; the mass ratio of the ball milling beads to the product of the primary calcination is 9:1; the temperature of the second drying treatment is 80°C, and the time is 12 hours; the secondary sintering treatment includes: pre-passing hydrogen and argon gas at room temperature for 1.5 hours, heating from room temperature to 600°C at a rate of 4°C / min, and calcining for 10 hours;

[0050] S3, dispersing the Mn-Ti co-doped sodium iron fluoride phosphate material in anhydrous ethanol and performing ultrasonic treatment to obtain a suspension;

[0051] S4, adding the rGO dispersion dropwise into the suspension (the mass ratio of Mn-Ti co-doped sodium fluoroferric phosphate material and rGO is 1:0.008), stirring continuously, and then sequentially performing hydrothermal treatment, washing treatment and a third drying treatment to obtain the rGO-coated Mn-Ti co-doped sodium fluoroferric phosphate material Na2Fe 0.88 Mn 0.08 Ti 0.04 PO4F@rGO; the temperature of the hydrothermal treatment is 130°C; and the reaction time is 7h.

[0052] Example 3

[0053] This embodiment provides another rGO-coated Mn-Ti co-doped sodium fluorophosphate material Na2Fe 0.93 Mn 0.05 Ti 0.02 The preparation method of PO4F@rGO comprises the following steps:

[0054] S1. Sodium acetate, ferrous sulfate, manganese dioxide, titanium dioxide, diammonium hydrogen phosphate and sodium fluoride are mixed in a molar ratio of 1:0.93:0.05:0.02:1:1, and the mixture is subjected to a first ball milling treatment, a first drying treatment and a pre-sintering treatment in sequence to obtain a first calcined product; the molar ratio of sodium, iron, manganese, titanium, phosphorus and fluorine in the mixture is 2:0.93:0.05:0.02:1:1; the rotation speed of the first ball milling treatment is 400 rpm, and the time is 7 hours; the mass ratio of ball milling beads to the mixture is 10:1; the temperature of the first drying treatment is 100°C, and the time is 10 hours; the pre-sintering treatment includes: pre-passing nitrogen at room temperature for 2 hours, heating from room temperature to 450°C at a rate of 5°C / min, and calcining for 3 hours;

[0055] S2, the product of the primary calcination is subjected to a second ball milling treatment, a second drying treatment and a second sintering treatment in sequence to obtain a Mn-Ti co-doped sodium ferric fluoride phosphate material; the rotation speed of the second ball milling treatment is 450rpm, and the time is 5h; the mass ratio of the ball milling beads to the product of the primary calcination is 10:1; the temperature of the second drying treatment is 100°C, and the time is 10h; the secondary sintering treatment includes: pre-passing nitrogen at room temperature for 2h, heating from room temperature to 650°C at a rate of 5°C / min, and calcining for 8h;

[0056] S3, dispersing the Mn-Ti co-doped sodium iron fluoride phosphate material in anhydrous ethanol and performing ultrasonic treatment to obtain a suspension;

[0057] S4, adding the rGO dispersion dropwise into the suspension (the mass ratio of Mn-Ti co-doped sodium fluoroferric phosphate material and rGO is 1:0.01), stirring continuously, and then sequentially performing hydrothermal treatment, washing treatment and a third drying treatment to obtain the rGO-coated Mn-Ti co-doped sodium fluoroferric phosphate material Na2Fe 0.93 Mn 0.05 Ti 0.02 PO4F@rGO; the temperature of the hydrothermal treatment is 140°C; and the reaction time is 6h.

[0058] Comparative Example 1

[0059] This comparative example provides another sodium fluorophosphate material, which is not coated with rGO compared with Example 1, and the rest is the same as Example 1.

[0060] Comparative Example 2

[0061] This comparative example provides another sodium fluorophosphate material, which is prepared by a conventional one-time sintering method, and the rest is the same as in Example 1.

[0062] Comparative Example 3

[0063] This comparative example provides another sodium fluorophosphate material, which is not doped with Mn and Ti during the preparation process, and the rest is the same as Example 1.

[0064] Detection Example

[0065] 1. Morphology test

[0066] SEM is the most basic test method for observing the microscopic morphology of materials. The Na2Fe 0.85 Mn 0.1 Ti 0.05 The surface morphology of PO4F@rGO was characterized. In order to improve the conductivity of the material and obtain a clearer scanning image, the material was sprayed with gold before testing.

[0067] The results are as follows Figure 2 As shown, Na2Fe 0.85 Mn 0.1 Ti 0.05 PO4F@rGO is a spherical particle with a diameter of 2-3 μm and a highly fluffy special morphology.

[0068] 2. Battery cycle performance test

[0069] In order to test the electrochemical properties of the material, the materials of Examples 1-3 and Comparative Examples 1-3 were used as the positive electrode to assemble half-cells for electrochemical performance tests. First, 175 mg of the material and 50 mg of SuperP were weighed respectively, ground in an agate mortar for about 20 min until fully mixed and then transferred to a paste bottle, 500 mg of the prepared 5wt% VDF NMP solution was added, and then about 800 μL of NMP solution was added, and magnetic stirring was performed for about 12 hours until a slightly viscous paste liquid was formed. Subsequently, a 120 μm scraper was used to evenly coat the paste on the aluminum foil, and vacuum dried at 120°C for 12 hours. The obtained positive electrode sheet was formed into a positive electrode sheet with a diameter of 12 mm by a sheet punching machine. With the electrode sheet as the positive electrode, the sodium sheet as the negative electrode, the glass fiber as the diaphragm, and the electrolyte selected as 1.0M NaClO4 / EC-PC (volume ratio 1:1, 5.0 Vol% FEC), CR2032 button batteries were assembled in a glove box filled with argon. The button cell is charged and discharged at a constant current of 0.2C (1C = 120mAh / g), with a voltage range of 2.0-4.0V. The charge and discharge curves of the button cell and the undoped Na2FePO4F are compared. Figure 3 The charge and discharge results are shown in Table 1.

[0070] Table 1

[0071]

[0072] Compared with the positive electrode materials without rGO coating (Comparative Example 1), directly using a single sintering method (Comparative Example 2) and not doped with Mn and Ti (Comparative Example 3), the present invention improves the electronic conductivity of the phosphate material by co-doping Mn-Ti on the basis of Na2FePO4F material, and at the same time enhances the structural stability of the material, so that the positive electrode active material has both high energy density and cycle stability. Among them, manganese doping can effectively improve the energy density of the material, and can be anchored between the lattices to widen the lattice size and increase the sodium ion transmission rate; low-valent titanium doping can stabilize the lattice structure and improve the cycle stability of the material. The two ball milling, sintering and hydrothermal reaction are combined to make the raw materials uniformly mixed and increase the contact area without being oxidized and deteriorated by air, which is conducive to efficient ion migration and lattice formation between the reactants, so that the F atoms with low reaction activity can also form stable chemical bonds, form a strong binding force with the phosphate group, inhibit the formation of pyrophosphate, and improve the purity and crystallinity of the material. And realize two-dimensional rGO coating on the material surface, which not only improves the electrical conductivity, but also can form a stable interface layer on the material surface, reduce the occurrence of interface side reactions, and improve the cycle stability.

[0073] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.

Claims

1. A rGO-coated Mn-Ti co-doped sodium fluorophosphate material, characterized in that: The chemical formula is Na2Fe x Mn y Ti z PO4F@rGO; wherein, 0.05≤y≤0.10, 0.02≤z≤0.05, x+y+z=1; Fe is +2 valence, Mn is +2 valence, and Ti is +2 valence.

2. A method for preparing the rGO-coated Mn-Ti co-doped sodium fluorophosphate material as claimed in claim 1, characterized in that the steps include: S1, after mixing a sodium source, an iron source, a manganese source, a titanium source, a phosphorus source and a fluorine source in proportion, the mixture is subjected to a first ball milling treatment, a first drying treatment and a pre-sintering treatment in sequence to obtain a primary calcined product; S2, subjecting the primary calcined product to a second ball milling treatment, a second drying treatment, and a second sintering treatment in sequence to obtain a Mn-Ti co-doped sodium fluoroferric phosphate material; S3, dispersing the Mn-Ti co-doped sodium iron fluoride phosphate material in anhydrous ethanol and performing ultrasonic treatment to obtain a suspension; S4. Add the rGO dispersion dropwise into the suspension while continuously stirring, and then sequentially perform hydrothermal treatment, washing treatment and a third drying treatment to obtain the rGO-coated Mn-Ti co-doped sodium iron fluoride phosphate material.

3. The preparation method according to claim 2, characterized in that: In step S1, the molar ratio of sodium, iron, manganese, titanium, phosphorus and fluorine in the mixture is 2:x:y:z:1:

1.

4. The preparation method according to claim 2, characterized in that: In step S1, the sodium source includes: at least one of sodium fluoride, sodium acetate, sodium carbonate, sodium citrate, and sodium oxalate; The iron source includes: at least one of ferrous oxalate, ferrous sulfate, and ferrous chloride; The manganese source includes: at least one of manganese dioxide, manganese trioxide, and manganese oxalate; The titanium source includes: at least one of titanium monoxide, titanium dioxide, titanium oxalate, and titanium sulfate; The phosphorus source includes: at least one of diammonium phosphate and diammonium hydrogen phosphate; The fluorine source includes at least one of sodium fluoride and hydrofluoric acid.

5. The preparation method according to claim 2, characterized in that: In step S1, the rotation speed of the first ball milling treatment is 300-500 rpm, and the time is 6-8 hours; the mass ratio of the ball milling beads to the mixture is (8-10): 1; The temperature of the first drying treatment is 60-100° C. and the time is 8-14 hours.

6. The preparation method according to claim 2, characterized in that: In step S1, the pre-sintering treatment includes: pre-passing protective gas at room temperature for 0.5-2 hours, heating from room temperature to 350-450° C. at a rate of 3-5° C. / min, and calcining for 2-6 hours; Wherein, the protective gas is at least one of argon, hydrogen argon, nitrogen and helium.

7. The preparation method according to claim 2, characterized in that: In step S2, the rotation speed of the second ball milling treatment is 400-500 rpm, and the time is 4-6 hours; the mass ratio of the ball milling beads to the first calcined product is (8-10): 1; The temperature of the second drying treatment is 60-100° C. and the time is 8-14 hours.

8. The preparation method according to claim 2, characterized in that: In step S2, the secondary sintering treatment includes: pre-passing protective gas at room temperature for 0.5-2 hours, heating from room temperature to 550-650° C. at a rate of 3-5° C. / min, and calcining for 8-12 hours; Wherein, the protective gas is at least one of argon, hydrogen argon, nitrogen and helium.

9. The preparation method according to claim 2, characterized in that: In step S4, the mass ratio of the Mn-Ti co-doped sodium iron fluoride phosphate material to rGO is 1: (0.005-0.01); The temperature of the hydrothermal treatment is 120-140° C. and the reaction time is 6-8 hours.

10. Use of the rGO-coated Mn-Ti co-doped sodium fluoroferric phosphate material as claimed in claim 1 or the rGO-coated Mn-Ti co-doped sodium fluoroferric phosphate material prepared by the preparation method according to any one of claims 2 to 9 in a positive electrode material for a sodium ion battery.

Citation Information

Patent Citations

  • Carbon-coated sodium ferric fluorophosphate material as well as preparation method and application thereof

    CN114242968A

  • Carbon-coated sodium-rich sodium ferric pyrophosphate composite positive electrode material, preparation method and application

    CN116169264A

  • Cr-doped composite positive electrode material and preparation method and application thereof

    CN117878277A

  • Monocrystal type ferric sodium pyrophosphate modified material as well as preparation method and application thereof

    CN117913274A

  • Polyanionic sodium ion battery positive electrode material, preparation method thereof and battery

    CN118712365A

Cited By

  • Graphene self-supporting intercalated sodium ferric manganese phosphate pyrophosphate positive electrode material and application thereof

    CN121583917A